Development of a rabbit monocyte activation test as an alternative to the rabbit pyrogen test and its application in the analysis of plasma-derived products. (June 2021) - Kim, Ji-Hye; Jung, Kikyung; Kim, Jaeok; Lee, Jiyoung; Kim, HyunJeong; Song, Hojin; Han, Kiwon; Park, Sangmi; Ahn, Chiyoung; Kim, Chan-Wha
Abstract: The rabbit pyrogen test (RPT) is a safety test conducted as a part of mandatory requirements of regulatory agencies. RPT is currently performed for routine quality control (QC) by manufacturers and for national lot release of biological products, such as plasma-derived products. However, RPT involves the use of many rabbits, counter to the international efforts to minimize the use of animals in research. Furthermore, pyrogen amount cannot be discerned from the test results and the results may be considerably affected by various factors. Therefore, a need exists for substituting RPT with in vitro assays. As a viable alternative to RPT, we here established a rabbit monocyte activation test (RMAT) based on the human MAT in the European Pharmacopoeia. RMAT uses rabbit peripheral blood mononuclear cells as the source of monocytes instead of live animals. The test detected endotoxin, lipoteichoic acid, peptidoglycan, and zymosan with high sensitivity, showing high correlation with the in vivo RPT results. The results of RMAT and RPT testing of non-pyrogenic plasma-derived products were also consistent. Furthermore, RMAT showed satisfactory recovery rates in an interference test with product samples and spiked-in pyrogens. We conclude that RMAT could replace the existing RPT for routine QC.